Association of ADIPOQ variants and heart failure in an Italian population. (June 2014) - Pileggi, Silvana; Barlera, Simona; Nicolis, Enrico; Crociati, Luisa; Pietri, Silvia; Specchia, Claudia; Franzosi, Maria Grazia
Objectives: Adiponectin has insulin-sensitizing, anti-inflammatory and anti-atherogenic properties. There are few and controversial data on the role of ADIPOQ variants in heart failure (HF) pathogenesis. We planned this large association study to investigate the potential association of four selected ADIPOQ polymorphisms with HF in a population of Italian origin. Methods: We genotyped 1173 cases with symptomatic HF and 1136 controls for alleles rs17300539, rs266729, rs1501299 and rs2241766. Cases were patients enrolled in the GISSI-Heart Failure genetic sub-study, with a long-term follow up (median 3.9 years). Controls were blood donors with no history of diabetes or cardiovascular disease (CVD). Genotype and allele frequencies of the four single nucleotide polymorphisms (SNPs) were compared between the two groups. Results: Clinical characteristics were significantly different between HF patients and controls. No significant differences were reported in the allelic and genotypic distribution, with the exception of rs266729 G allele, which showed a significant association with an increased risk of HF [odds ratio (OR) = 1.26; 95% confidence interval (CI) = 1.07–1.48; p = 0.006). We divided the GISSI-HF population according to HF etiology (ischemic and nonischemic) and presence of diabetes. For rs266729 G allele, a significant association with HF was confirmed in both ischemic (OR = 1.29; 95% CI = 1.06–1.56; p = 0.009) and nonischemic patients (OR = 1.2; 95% CI = 1.02–1.42; p = 0.03) as well as in nondiabetic patients (OR = 1.25; 95% CI = 1.05–1.49; p = 0.012). rs2241766 G allele showed a significant reduction of risk of HF in nonischemic (OR = 0.77; 95% CI = 0.62–0.95; p = 0.02) and diabetic patients (OR = 0.62; 95% CI = 0.45–0.84; p = 0.0025). Conclusions: We confirm the association between rs266729 G allele and an increased risk of HF and between rs2241766 G allele and decreased risk of HF. Our study extends the knowledge on the influence of ADIPOQ variants on CVD.